Length–weight relationships of four indigenous freshwater fish species from Khalsi wetland in lower Ganga basin, West Bengal, India. (2nd February 2016) - Sandhya, K. M.; Hassan, M. A.; Kumari, S.; Mishal, P.; Lianthuamluaia, L.; Kumar, V.; Aftabuddin, M.; Meena, D. K.
Summary: The length‐weight relationships of four indigenous freshwater fishes Parambassis lala (Hamilton, 1822), Trichogaster lalius (Hamilton, 1822), Puntius terio (Hamilton, 1822), and Pethia phutunio (Hamilton, 1822) were determined. Fish samples were collected during December 2013 to May 2015 from Khalsi, a floodplain wetland along the tributary of the River Ganges in West Bengal state, India using different types of gear (castnets, gillnets and drag nets, stretched mesh sizes of 15–20 mm, 20–30 mm and 5–10 mm, respectively). This is the first report on the length–weight relationship parameters of these four species.